The Existence of the Indonesian Christian Church (GKI) Bondowoso, 1962-2019 - Salindri, Dewi; Widuatie, Ratna Endang; Arta, Wana (Indonesian Historical Studies, 2024)
This article presents a historical analysis of the growth of GKI Bondowoso, a Protestant Christian church in Indonesia. Employing a sociological approach and functionalism theory, to analyze the social functions of the church within its community as well as the interactions between the church and other social institutions. GKI Bondowoso, established on a land grant from a Muslim community, has a unique history. It became a founding member of the seven church clusters that led to the formation of GKI East Java. Since 1962, the church has strived for self-sufficiency and actively participated in the efforts to unify the GKI into a single organization. Throughout its history, GKI Bondowoso has experienced changes in pastoral leadership and commission activities. It has actively sought to positively influence its surrounding environment, including fostering integration with the ethnic Chinese community and learning about Madurese customs. The ethnic Chinese population in Bondowoso has successfully adopted the local language, facilitating better relationships within the community. However, the church's growth and sustainability have been supported by its positive relationships with the local community and other religious groups, demonstrating its positive influence on its environment.